074 The prevalence and significance of left ventricular hypertrabeculation in highly trained athletes. (16th May 2012) - Gati, S; Chandra, N; Bennett, R L; Reed, M; Gaelle, K; Papadakis, M; Panoulas, V F; Chen, L; Carrie, F; Sharma, S
Abstract : Introduction: Left ventricular non-compaction (LVNC) cardiomyopathy is characterised by increased myocardial trabeculation and recesses. Clinical manifestations of the disorder include progressive left ventricular dilatation, systolic impairment, predilection to fatal arrhythmias and thrombo-embolic events. Studies in heart failure patients demonstrate a high prevalence (up to 30%) of myocardial trabeculations irrespective of the criterion used, and raise the potential diagnosis of LVNC. Given the high prevalence compared with other primary cardiomyopathies, it is unclear whether the myocardial morphology is representative of LVNC or merely an epiphenomenon associated with increased cardiac preload. The large cardiac preload associated with regular participation of intensive exercise results in physiological cardiac remodelling including increased left ventricular wall thickness and cavity size. Isolated case findings have also revealed increased trabeculations in some athletes but the significance of the anomaly is unclear. The distinction between cardiac remodelling from athletic training and LVNC is important when one considers that primary cardiomyopathies are the most commonly implicated cause of exercise related sudden cardiac death in young athletes. The aim of this study was to identify the prevalence and significance of hypertrabeculation in highly trained young athletes. Method: Between 2003 and 2011, 1146 athletes, aged 14–35 years, underwent 12-lead ECG and echocardiography. Echocardiograms were analysed in accordance with ASE guidelines and hypetrabeculation was defined as >3 localised protrusions of the ventricular wall >3 mm in thickness associated with intertrabecular recesses. Results were compared with 415 healthy controls of similar age. Results: Athletes displayed a higher prevalence of LV HTC compared with controls (18.3% vs 9.0%; p<0.0001). Of the athletes, 10.1% fulfilled conventional criteria for LVNC. African/Afro-Caribbean athletes exhibited a higher prevalence of LV HTC compared with Caucasians (28.8% vs 16.3%; p=0.002). Left ventricular hypertrabeculation was associated with T-wave inversion and lower indices of systolic function, however, assessment with 48 h ECG, exercise stress test and cardiac MRI failed to identify broader features of LVNC phenotype. Follow-up during the ensuing 48.6±14.6 months did not reveal adverse events. Conclusion: The high prevalence of LV HTC in athletes, particularly among African/Afro-Caribbean athletes, suggests that the morphological anomaly represents an ethnically determined physiological epiphenomenon secondary to increased cardiac preload and afterload. Associated marked repolarisation changes and lower LV fractional shortening cannot exclude a myocardial disorder in a small minority. Prolonged longitudinal follow-up in a larger cohort of athletes should identify the precise significance of LV HTC.